PENGARUH KONTROL DIRI DAN LINGKUNGAN KERJA TERHADAP STRES KERJA GURU SMA NEGERI DI KECAMATAN KAMPAR - HAIRUS HAIRUS; ISJONI ISJONI; AZHAR AZHAR (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
The aim of this research is to know about the influence between variables (1)self control toward teacher work stress in senior high schools of Kampar Sub district , (2) workenvironment toward teacher work stress in senior high schools of Kampar Sub district, (3) selfcontrol and work environment together toward teacher work stress in senior high schools ofKampar Sub district . This research carried out by spreading the instruments for 92 teachers insenior high school of Kampar Sub district by using proportionate random sampling technique.The instrument used to collect the data of all variables using the questionnaire. Validity wastested using Pearson product moment formula. Instrument reliability coefficient was calculatedusing Cronbach alpha formula. The results showed a positive relationship between: (1) There isa positive influence between self controltoward teacher work stress in senior high school ofKampar Sub district with a correlation coefficient rx1. y = 0,068 and the regression equation v= 65,00 - 0,093 X1. (2) There is a positive influence between work environment toward teacherwork stressin senior high schools of Kampar Sub district with correlation coefficients rx2. y=0,068 and the regression v = 64,272 - 0,078 X2. (3) There is a positive influence between selfcontrol and work environment toward teacher work stress in senior high school of Kampar Subdistrict with Rx1 x2.y multiple correlation coefficient = 0,089 and the regression equation v =70,20 - 0,079 X1 - 0,066 X22. The results of this study are expected to be useful for theimprovement and reduction of work stress in senior high school of Kampar Sub district byincreasing self control and work environment.